2014
DOI: 10.1097/01.tp.0000436927.08026.a8
|View full text |Cite
|
Sign up to set email alerts
|

Increased Negative Impact of Donor HLA-Specific Together With Non-HLA–Specific Antibodies on Graft Outcome

Abstract: These results show the increased negative impact of dnDSA and AT1R-ab on freedom from AMR and/or CMR and an increased hazard ratio when both parameters are considered. Both HLA- and non-HLA-specific antibodies seem to impact graft outcome in heart transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(78 citation statements)
references
References 47 publications
3
74
0
1
Order By: Relevance
“…[32][33][34][35][36] We also reported an increased negative impact of antibodies to angiotensin type 1 receptor along with de novo donor HLA specific antibody on heart allograft outcome. 37 There is increasing evidence that antibodies to HLA and non-HLA work in concert toward an increased negative impact on graft dysfunction. [37][38][39][40] In conclusion, we have developed an algorithm to prioritize the assignment of UAs allowing sensitized patients to receive transplants at a rate higher than on the national waitlist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[32][33][34][35][36] We also reported an increased negative impact of antibodies to angiotensin type 1 receptor along with de novo donor HLA specific antibody on heart allograft outcome. 37 There is increasing evidence that antibodies to HLA and non-HLA work in concert toward an increased negative impact on graft dysfunction. [37][38][39][40] In conclusion, we have developed an algorithm to prioritize the assignment of UAs allowing sensitized patients to receive transplants at a rate higher than on the national waitlist.…”
Section: Discussionmentioning
confidence: 99%
“…37 There is increasing evidence that antibodies to HLA and non-HLA work in concert toward an increased negative impact on graft dysfunction. [37][38][39][40] In conclusion, we have developed an algorithm to prioritize the assignment of UAs allowing sensitized patients to receive transplants at a rate higher than on the national waitlist. The outcomes show some increased negative impact on freedom from rejection (AMR and CMR) depending on the pre-transplant status of DSA and crossmatch positivity.…”
Section: Discussionmentioning
confidence: 99%
“…With regards that the detection of HLA and non-HLA antibodies specific to donor (DSA) is critical finding to predict alloimmune response to kidney allograft, particularly antibody mediated rejection (AMR) (12)(13)(14), understanding the significance of various aspects of each test and utilization of tests in different stages of kidney transplantation (flow KT) would have significant importance.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors recently reported that a high PRA level, especially positive donor-specific antibody (DSA), was associated with not only AMR but also ACR. 23,24) Loupy, et al demonstrated that very late rejection at several years after HTx diagnosed as ≥ 2R ISHLT rejection was associated with complement-cascade activation and microvascular injury along with positive DSA, suggesting accompanied antibody-mediated process. 25) C4d deposition observed in all 5 LR (+) recipients at the time of LR was compatible with the finding of Loupy and coworkers that LR might have a component of the antibody-mediated process in addition to cellular rejection.…”
Section: Discussionmentioning
confidence: 99%